OPTICAL IMAGE INFORMATIVITY IN OPTIC AND ELECTRONIC DEVICES LIMITED BY ABERRATIONS: OPTICAL IMAGE INFORMATIVITY IN OPTIC AND ELECTRONIC DEVICES LIMITED BY ABERRATIONS - Getsov, Petar; Zhekov, Zhivko; Mardirossian, Garo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Some interrelations of two dimensional image entropy of optic and electronic devices are developed in this paper. The informativity of the object image is investigated through the use of multi spectral optic system, limited by aberations.